Nanoscale magnetization reversal by electric field-induced ion migration. (17th September 2018) - Chen, Qilai; Liu, Gang; Gao, Shuang; Yi, Xiaohui; Xue, Wuhong; Tang, Minghua; Zheng, Xuejun; Li, Run-Wei
Abstract: Abstract : Nanoscale magnetization modulation by electric field enables the construction of low-power spintronic devices for information storage applications and, etc. Electric field-induced ion migration can introduce desired changes in the material's stoichiometry, defect profile, and lattice structure, which in turn provides a versatile and convenient means to modify the materials' chemical-physical properties at the nanoscale and in situ. In this review, we provide a brief overview on the recent study on nanoscale magnetization modulation driven by electric field-induced migration of ionic species either within the switching material or from external sources. The formation of magnetic conductive filaments that exhibit magnetoresistance behaviors in resistive switching memory via foreign metal ion migration and redox activities is also discussed. Combining the magnetoresistance and quantized conductance switching of the magnetic nanopoint contact structure may provide a future high-performance device for non-von Neumann computing architectures.